Spatiotemporal analysis of agricultural drought and its relationship with climate variabilities in the growing season of the Horn of Africa - Maniraho, Albert Poponi; Lanhai, Li; Bai, Jie; Edwin, Igboeli Emeka; Nzabarinda, Vincent; Fabien, Muhirwa; Izere, David; Niyomugabo, Pauline; Umugwaneza, Adeline; Bakayisire, Fabiola (Frontiers in Climate, 2026)
This study investigates agricultural drought dynamics in the Horn of Africa (HoA) during the June–August growing seasons from 1995 to 2020. Using MODIS and GIMMS NDVI3g data, we derived the Vegetation Condition Index (VCI) to quantify patterns and identify climatic drivers. To delineate persistent drought vulnerability hotspots, we integrated temperature, precipitation, and VCI data, supplemented by satellite-derived soil moisture data, with a season-specific Weighted Overlay Index (WOI). Results revealed significant interannual variability in growing-season conditions, with widespread greenness in 1997–1998 contrasting with severe droughts in 2004, 2009, and 2011, the latter affecting up to 27.3% of the region. Drought hotspots were identified across northern Kenya, eastern Ethiopia, and central Somalia. Trend analysis indicates an increase in extreme and severe drought from 1995 to 2011, followed by partial contraction, though baseline drought exposure remains elevated. Climate data reveals significant spatial variability in precipitation and temperature, with a strong positive correlation between VCI and precipitation (R2 = 0.73) and a negative correlation with temperature (R2 = −0.74). Vulnerability assessment highlights western Ethiopia as highly vulnerable. Correlation analysis between VCI and detrended maize yield showed positive relationships, strongest in Ethiopia (R = 0.353) and Kenya (R = 0.415), validating VCI as an indicator of drought impact on crop performance. The findings underscore increasing drought frequency and the need for climate-resilient agricultural planning in the HoA.